Indicators of social and emotional health competence of education department administrators: a case study in Bandar Abbas - Shahpari Zakeri Dehvostanezhad; Mahmoud Sabahizadeh; Kolsum Nami; Nadergholi Ghourchian (Shahid Beheshti University of Medical Sciences, 2023)
Background: This study was conducted with the aim of identifying indicators of social and emotional health competence of managers of education departments, as a case study of Bandar Abbas city. Methods: This study was applied research conducted by descriptive-correlational method. In the first section, using content analysis method (interview with experts), 20 experts attend in the field of educational sciences and educational management. In the second, to design a structural-interpretive model, 15 experts were used to answer the questionnaire. Data collection was performed by a researcher-made questionnaire. The reliability of the questionnaire was confirmed by Cronbach's alpha coefficient, composite reliability coefficient and factor loads. The validity of the questionnaire was confirmed by content and construct validity. Analysis of descriptive indices and correlation matrix between them were performed with SPSS and model fit was examined with Smart PLS software. Results: Factors affecting social and emotional competencies have high influence. Professional competencies, especially basic and teaching-related competencies have a significant effect on teachers' educational performance. Themes include 8 main variables about quality of work life, protectionism, realism, trust building, social commitment, job competence, individual and social competence. Weak, medium and strong value of the structural part of the model is determined by criterion of R2 were 0.19, 0.33 and 0.33. Conclusion: Emotional and social functioning and concurrent conditions among education and referral managers for the implementation of evidence-based interventions may be useful for the overall performance. The results of study are useful for improving the emotional and social skills of education managers.